The effect of waves in hydrodynamics, stratification, and salt wedge intrusion in a microtidal estuary - Higgins Álvarez, Aldemar; Otero, Luis; Restrepo, Juan Camilo; Álvarez, Oscar (Frontiers in Marine Science, 2022)
Waves have been found to modulate circulation, stratification, and sediment dynamics in several estuaries, mainly near the mouth. This study analyzes the effects of waves on the hydrodynamics, stratification process, and dynamics of the salt wedge in an estuary with a microtidal range, high fluvial and sediment discharges, and dominated by waves: the Magdalena River estuary (MRE). It is, under low flow conditions, a highly stratified, salt wedge type. Field measurements and the MOHID 3D modeling system, 2D coupled with the SWAN model, were used for this purpose. The low flow seasons of 2018 (February-March) and 2020 (March) were taken as case studies. Results show that when considering wave effects in the numerical simulations, more realistic conditions are reproduced in the circulation patterns and salinity distribution in the outer estuary. Variations in velocity patterns and salinity distribution are found between the mouth and 2 km upstream of the mouth when comparing the simulations with and without waves, especially in the mixing layer. These variations in hydrodynamics and stratification may be associated with increased wave-induced bed shear stress, variations in barotropic and baroclinic acceleration, and increased vertical mixing. At 2 km into the river channel, the reduction in wave height energy of 95% and changes in salinity distribution are already lower than 2%. In addition, it was observed that waves do not generate significant changes in the dynamics of the salt wedge, which is mainly affected by the diurnal tidal cycle, presenting variations in the length of the intrusion of up to 1 km, and in the magnitude of the longitudinal salinity gradient at the salt front, presenting low salinities at high tide when the wedge enters, and high salinities at low tide, in its retreat.